New Insights into Fundamental Processes and Physical Degradation Mechanisms in Rechargeable Lithium‐Oxygen Batteries Providing Suitably High Energy Densities - Shoichi Matsuda (ChemElectroChem, 2024)
Abstract Lithium‐oxygen batteries (LOBs) can exhibit high energy densities and so have attracted much attention as next‐generation energy storage devices. Although 500 Wh/kg LOBs have recently been demonstrated, the performance of these batteries could still be greatly improved. This Concept article highlights the importance of exploring new technologies, such as gas‐diffusion layers and lightweight protective membranes for lithium metal electrodes, as an approach to realizing LOBs having energy densities sufficient for practical applications. In addition, the physical degradation phenomenon specific to LOBs designed with high energy density is also introduced, such as the volume change of the positive electrode and the movement of the electrolyte associated with the progress of repeated discharge/charge cycles. We believe that the topics presented in this article will promote new research directions in the future development of high energy density and long cycle life LOB.